Cement-based self-leveling filling binding material and construction method thereof
By using cement-based self-leveling fill bonding materials, the problem of existing mortars being difficult to separate when the assembly block is replaced is solved, convenient connection and disassembly of assembly blocks is achieved, and construction efficiency and maintenance are improved.
Patent Information
- Application Number
- CN202510076917.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
AI Technical Summary
The existing mortar is difficult to separate when the assembly block is replaced, which affects construction efficiency and maintenance.
Cement-based self-leveling fill bonding material is used, which consists of cement, gypsum powder, vitrified microbeads, glass powder, bean dregs, cellulose and polycarboxylic acid ether. The strength of the material after wetting is reduced through the complexation of bean dregs and microbeads, making it easier to disassemble.
It realizes convenient connection and disassembly between assembly blocks and between assembly blocks and the outside, improving construction efficiency and maintenance.
Abstract
Description
Technical Field
[0001] The present application relates to a cement-based self-leveling filling bonding material and a construction method thereof. Background Art
[0002] Assembled floor heating pipe assembly blocks refer to the method of setting floor heating pipe grooves in the assembly blocks, prefabricating the assembly blocks, and then introducing mortar between the assembly blocks. The introduced mortar needs to have the function of bonding the assembly blocks and filling the gap between the assembly blocks and the ground base. This requires the mortar to have good fluidity, adhesion, and no cracking after drying. The existing mortar can basically meet the above requirements. However, since there are two purposes for using assembly blocks, one is to speed up the construction progress and improve construction efficiency; the other is to be able to replace them when they are damaged or the house is renovated. The existing mortar can generally only bond the products together, and it is actually difficult to separate them when replacing them. Summary of the invention
[0003] In order to solve the above problems, the present application proposes a cement-based self-leveling filling adhesive material, comprising the following raw materials in parts by weight:
[0004] Cement: 180-200 parts;
[0005] Gypsum powder: 4-6 parts;
[0006] Vitrified microspheres: 6-8 parts;
[0007] Glass powder: 8-10 parts;
[0008] Okara: 4-6 portions;
[0009] Cellulose: 0.5-0.8 parts;
[0010] Polycarboxylate ether: 0.3-0.5 parts. The filling adhesive material used in the present application is mainly used for connection between assembly blocks and between assembly blocks and the outside, and needs to be able to play the role of leveling and connection, and after use, it needs to be able to be disassembled for later maintenance and replacement.
[0011] Preferably, the water-to-material ratio of the filling adhesive material is 0.3-0.4:1.
[0012] Preferably, the particle size of the vitrified microspheres is 10-100 μm;
[0013] The cellulose is glass fiber, and the diameter of the glass fiber is 10-20 μm and the length is 2-5 mm.
[0014] Preferably, the glass powder is obtained by crushing silicate glass, and then sieving to obtain particles with a particle size between 20 mesh and 50 mesh.
[0015] Preferably, the bean dregs are obtained in the following manner:
[0016] Soaking and grinding the soybeans and filtering them to obtain a filter residue;
[0017] The filtered residue is dried and then ground through a 200-mesh sieve, and the sieved material is taken to obtain bean dregs. The present application reduces the strength of the filling adhesive material after wetting through the composite effect of bean dregs, vitrified microbeads, and glass powder, making it easier to operate when it needs to be removed, and the glass microbeads and glass powder can play an isolation role.
[0018] Preferably, the flexural strength of the mortar board obtained by pouring the filling adhesive material after being fully moistened is 1 / 3-1 / 2 of that in the dry state.
[0019] On the other hand, the present application also proposes a construction method of a cement-based self-leveling filling adhesive material, comprising the following steps:
[0020] Lay the assembly blocks on the ground and level the assembly blocks;
[0021] preparing a filling bonding material;
[0022] Pour the filling adhesive material into the gap between the lower part of the assembly block and the ground, the gap between the assembly blocks, and the gap between the side of the edge assembly block and the wall;
[0023] After maintenance, install the floor heating pipes on the assembly blocks.
[0024] Preferably, an introduction channel for introducing filling adhesive material is reserved in the middle of the assembly block.
[0025] Preferably, the filling adhesive material is prepared as follows:
[0026] The cement, gypsum powder, vitrified microspheres and glass powder are fully mixed to obtain a first component;
[0027] Adding dregs of soybeans, cellulose and polycarboxylate ether into water and mixing them thoroughly to obtain a second component;
[0028] The first component and the second component are mixed to obtain a filling adhesive material. The present application mixes bean dregs, cellulose, and polycarboxylate ether into water. In this way, the uniformity of the cellulose mixture can be ensured, and the bean dregs and polycarboxylate ether are distributed in agglomerates based on the cellulose. During the synthesis, the strength of the concrete is ensured. In the later stage, the strength of the adhesive material obtained by the filling adhesive material under wet conditions can be reduced, which is convenient for disassembly.
[0029] Preferably, an adjusting bolt for adjusting the height is provided under the assembly block or a bottom supporting leg is provided at the bottom of the assembly block.
[0030] This application can bring the following beneficial effects:
[0031] 1. The filling adhesive material used in this application is mainly used for the connection between assembly blocks and between assembly blocks and the outside. It needs to be able to play a leveling and connecting role, and after use, it also needs to be able to be disassembled for later maintenance and replacement.
[0032] 2. This application reduces the strength of the filling adhesive material after wetting through the composite effect of bean dregs, vitrified microbeads and glass powder, making it easier to operate when removal is required, and the glass microbeads and glass powder can play an isolating role.
[0033] 3. The present application mixes bean dregs, cellulose and polycarboxylate ether into water. In this way, the uniformity of the cellulose mixing itself can be ensured, while the bean dregs and polycarboxylate ether are distributed in clusters based on the cellulose. During the synthesis, the strength of the concrete is ensured. In the later stage, the strength of the adhesive material obtained by filling the adhesive material under wet conditions can be reduced, which is convenient for disassembly. DETAILED DESCRIPTION
[0034] In order to clearly illustrate the technical features of this solution, this application is elaborated in detail below through specific implementation methods.
[0035] This application is actually a filling adhesive material and a method of using the same. For the cement-based foamed self-leveling filling adhesive material, it includes the following raw materials in parts by mass:
[0036] Cement: 180-200 parts;
[0037] Gypsum powder: 4-6 parts;
[0038] Vitrified microspheres: 6-8 parts;
[0039] Glass powder: 8-10 parts;
[0040] Okara: 4-6 portions;
[0041] Cellulose: 0.5-0.8 parts;
[0042] Polycarboxylate ether: 0.3-0.5 parts.
[0043] The water-to-material ratio of the filling adhesive material is 0.3-0.4:1.
[0044] The particle size of the vitrified microspheres is 10-100 μm;
[0045] The cellulose is glass fiber, and the diameter of the glass fiber is 10-20 μm and the length is 2-5 mm.
[0046] The glass powder is obtained by crushing silicate glass, and then sieving to obtain particles with a particle size between 20 mesh and 50 mesh.
[0047] The bean dregs are obtained in the following manner:
[0048] Soaking and grinding the soybeans and filtering them to obtain a filter residue;
[0049] The filtered residue is dried and then ground to pass through a 200-mesh sieve, and the sieved material is taken to obtain bean dregs.
[0050] The flexural strength of the mortar board obtained by pouring the filling adhesive material after being fully moistened is 1 / 3-1 / 2 of that in the dry state.
[0051] The construction method of filling bonding materials includes the following steps:
[0052] S1: Lay the assembly block on the ground and level the assembly block;
[0053] An introduction channel for introducing filling adhesive material is reserved in the middle of the assembly block;
[0054] An adjusting bolt for adjusting the height is arranged under the assembly block or a bottom supporting leg is arranged at the bottom of the assembly block.
[0055] S2 prepares filling and bonding materials;
[0056] The filling bonding material is prepared as follows:
[0057] Fully mix 180-200 parts of cement, 4-6 parts of gypsum powder, 6-8 parts of vitrified microspheres, and 8-10 parts of glass powder to obtain a first component;
[0058] 4-6 parts of bean dregs, 0.5-0.8 parts of cellulose, and 0.3-0.5 parts of polycarboxylate ether are added into water with a water-to-material ratio of 0.3-0.4:1 and then fully mixed to obtain a second component;
[0059] The first component and the second component are mixed to obtain a filling bonding material.
[0060] The particle size of the vitrified microspheres is 10-100 μm;
[0061] The cellulose is glass fiber, and the diameter of the glass fiber is 10-20 μm and the length is 2-5 mm.
[0062] The glass powder is obtained by crushing silicate glass, and then sieving to obtain particles with a particle size between 20 mesh and 50 mesh.
[0063] The bean dregs are obtained as follows:
[0064] Soaking and grinding the soybeans and filtering them to obtain a filter residue;
[0065] The filtered residue is dried and then ground to pass through a 200-mesh sieve, and the sieved material is taken to obtain bean dregs.
[0066] S3: pouring the filling adhesive material into the gap between the lower part of the assembly block and the ground, the gap between the assembly blocks, and the gap between the side of the edge assembly block and the wall;
[0067] After S4 maintenance, install floor heating pipes on the assembly blocks.
[0068] In order to demonstrate the reliability of the present application, the following examples and comparative examples are prepared.
[0069] The assembly block is prepared as follows:
[0070] S11 sets the skeleton structure and sets the skeleton structure into the mold;
[0071] The skeleton structure comprises four vertical rods arranged vertically, and four circularly arranged transverse reinforcing rods connected in sequence are arranged between the vertical rods.
[0072] The vertical rod is hollow, and a height adjustment rod is connected to the vertical rod through internal threads.
[0073] The transverse reinforcing rod is located in the middle concrete.
[0074] S12: concrete is introduced into the mold (the length and width of the middle part of the mold is 500mm*500mm and the thickness is 40mm) and then cured;
[0075] When pouring, first pour the first thickness of 10mm of the introduced concrete, then pour the second thickness of 20mm of the middle concrete, and then pour the third thickness of 10mm of the introduced concrete. After curing, the assembled floor tiles are obtained.
[0076] The introduced concrete is firstly prepared by mixing 3 parts of cement, 1.5 parts of fly ash, 60 parts of perlite, 15 parts of sodium silicate, 1 part of polycarboxylate water reducer, 0.5 parts of sodium stearate and 0.4 parts of cellulose to obtain dry material, and then adding 2 parts of hydrogen peroxide with a water-to-material ratio of 0.6:1 to water, and then mixing with the dry material to obtain the introduced concrete. The introduced concrete includes the following raw materials in parts by weight:
[0077] The content of the hydrogen peroxide is 80wt%; the cellulose is glass fiber, the diameter of the glass fiber is 10-20μm, and the length is 3-5mm.
[0078] The middle concrete is firstly prepared by mixing 3 parts of cement, 1.5 parts of fly ash, 60 parts of perlite, 15 parts of sodium silicate, 1 part of polycarboxylate water reducer, 0.5 parts of sodium stearate, 0.4 parts of cellulose and 0.3 parts of manganese dioxide to obtain dry material, and then adding 2 parts of hydrogen peroxide with a water-to-material ratio of 0.6:1 to water, and then mixing with the dry material to obtain the middle concrete. The middle concrete includes the following raw materials in parts by weight:
[0079] The content of the hydrogen peroxide is 80wt%; the cellulose is glass fiber, the diameter of the glass fiber is 10-20μm, and the length is 3-5mm.
[0080] A convex ring for forming a pipe groove on the floor tile is arranged on the upper mold, and a 10 mm annular groove is arranged in the middle, and the diameter of the annular groove is 1 m.
[0081] After S13 curing, the mold is removed to obtain the assembly block;
[0082] Place the template with the above materials indoors at a room temperature not lower than 10°C and demould after curing for 10 days.
[0083] Embodiment 1:
[0084] S101 Lay 8 assembly blocks on the ground in a 4x2 pattern and level the assembly blocks, leaving a 10mm gap between each assembly block;
[0085] The middle part of the assembly block is firstly provided with an introduction channel for introducing the filling adhesive material;
[0086] An adjusting bolt for adjusting the height is arranged under the assembly block so that there is a gap of 5 mm between the bottom block and the ground.
[0087] S102 prepares a filling bonding material;
[0088] The filling bonding material is prepared as follows:
[0089] 180 parts of cement, 4 parts of gypsum powder, 6 parts of vitrified microspheres, and 8 parts of glass powder are fully mixed to obtain a first component;
[0090] 4 parts of bean dregs, 0.5 parts of cellulose, and 0.3 parts of polycarboxylate ether are added into water with a water-to-material ratio of 0.4:1 and then fully mixed to obtain a second component;
[0091] The first component and the second component are mixed to obtain a filling bonding material.
[0092] The particle size of the vitrified microspheres is 10-100 μm;
[0093] The cellulose is glass fiber, and the diameter of the glass fiber is 10-20 μm and the length is 2-5 mm.
[0094] The glass powder is made by crushing silicate glass, and then sieving to obtain particles with a particle size between 20 mesh and 50 mesh.
[0095] The bean dregs are obtained as follows:
[0096] Soaking and grinding the soybeans and filtering them to obtain a filter residue;
[0097] The filtered residue is dried and then ground to pass through a 200-mesh sieve, and the sieved material is taken to obtain bean dregs.
[0098] S103: pouring the filling adhesive material into the gap between the lower part of the assembly block and the ground, the gap between the assembly blocks, and the gap between the side of the edge assembly block and the wall;
[0099] S104 is cured, the curing temperature cannot be lower than 15℃, and the curing time is 10 days.
[0100] First, separate the assembly blocks using a cutting machine, and use a lever to lift the outermost assembly block to measure the force applied, which is 542N.
[0101] The entire space was moistened for 24 hours, and the assembly block on the other side was lifted up with a lever to measure the applied force, which was 183N.
[0102] Embodiment 2:
[0103] S201 Lay 8 assembly blocks on the ground in a 4x2 pattern and level the assembly blocks, leaving a 10mm gap between each assembly block;
[0104] The middle part of the assembly block is firstly provided with an introduction channel for introducing the filling adhesive material;
[0105] An adjusting bolt for adjusting the height is arranged under the assembly block so that there is a gap of 5 mm between the bottom block and the ground.
[0106] S202 prepares a filling bonding material;
[0107] The filling bonding material is prepared as follows:
[0108] Fully mix 200 parts of cement, 6 parts of gypsum powder, 8 parts of vitrified microspheres, and 10 parts of glass powder to obtain a first component;
[0109] 6 parts of bean dregs, 0.8 parts of cellulose, and 0.5 parts of polycarboxylate ether are added into water with a water-to-material ratio of 0.3:1 and then fully mixed to obtain a second component;
[0110] The first component and the second component are mixed to obtain a filling bonding material.
[0111] The particle size of the vitrified microspheres is 10-100 μm;
[0112] The cellulose is glass fiber, and the diameter of the glass fiber is 10-20 μm and the length is 2-5 mm.
[0113] The glass powder is made by crushing silicate glass, and then sieving to obtain particles with a particle size between 20 mesh and 50 mesh.
[0114] The bean dregs are obtained as follows:
[0115] Soaking and grinding the soybeans and filtering them to obtain a filter residue;
[0116] The filtered residue is dried and then ground to pass through a 200-mesh sieve, and the sieved material is taken to obtain bean dregs.
[0117] S203: pouring the filling adhesive material into the gap between the lower part of the assembly block and the ground, the gap between the assembly blocks, and the gap between the side of the edge assembly block and the wall;
[0118] S204 is cured, the curing temperature cannot be lower than 15℃, and the time is 10 days.
[0119] First, separate the assembly blocks using a cutting machine, and use a lever to lift the outermost assembly block to measure the force applied, which is 589N.
[0120] The entire space was moistened for 24 hours, and the assembly block on the other side was lifted up with a lever to measure the applied force, which was 260N.
[0121] In order to demonstrate the effectiveness of this application, the following comparative examples are made:
[0122] Comparative Example 1:
[0123] S301 Lay 8 assembly blocks on the ground in a 4x2 pattern and level the assembly blocks, leaving a 10mm gap between each assembly block;
[0124] The middle part of the assembly block is firstly provided with an introduction channel for introducing the filling adhesive material;
[0125] An adjusting bolt for adjusting the height is arranged under the assembly block so that there is a gap of 5 mm between the bottom block and the ground.
[0126] S302 prepares filling bonding material;
[0127] The filling bonding material is prepared as follows:
[0128] 180 parts of cement, 4 parts of gypsum powder, 6 parts of vitrified microspheres, and 8 parts of glass powder are fully mixed to obtain a first component;
[0129] 0.5 parts of cellulose and 0.3 parts of polycarboxylate ether are added into water with a water-to-material ratio of 0.4:1 and then fully mixed to obtain a second component;
[0130] The first component and the second component are mixed to obtain a filling bonding material.
[0131] The particle size of the vitrified microspheres is 10-100 μm;
[0132] The cellulose is glass fiber, and the diameter of the glass fiber is 10-20 μm and the length is 2-5 mm.
[0133] The glass powder is made by crushing silicate glass, and then sieving to obtain particles with a particle size between 20 mesh and 50 mesh.
[0134] S303: pouring the filling adhesive material into the gap between the lower part of the assembly block and the ground, the gap between the assembly blocks, and the gap between the side of the edge assembly block and the wall;
[0135] S304 is cured, the curing temperature cannot be lower than 15℃, and the time is 10 days.
[0136] First, separate the assembly blocks using a cutting machine, and use a lever to lift the outermost assembly block to measure the force applied, which is 725N.
[0137] The entire space was moistened for 24 hours, and the assembly block on the other side was lifted up with a lever to measure the applied force, which was 690N.
[0138] Comparative Example 2:
[0139] S401 Lay 8 assembly blocks on the ground in a 4x2 pattern and level the assembly blocks, leaving a 10mm gap between each assembly block;
[0140] The middle part of the assembly block is firstly provided with an introduction channel for introducing the filling adhesive material;
[0141] An adjusting bolt for adjusting the height is arranged under the assembly block so that there is a gap of 5 mm between the bottom block and the ground.
[0142] S402 prepares a filling bonding material;
[0143] The filling bonding material is prepared as follows:
[0144] 180 parts of cement, 4 parts of gypsum powder, and 6 parts of vitrified microspheres are fully mixed to obtain a first component;
[0145] 4 parts of bean dregs, 0.5 parts of cellulose, and 0.3 parts of polycarboxylate ether are added into water with a water-to-material ratio of 0.4:1 and then fully mixed to obtain a second component;
[0146] The first component and the second component are mixed to obtain a filling bonding material.
[0147] The particle size of the vitrified microspheres is 10-100 μm;
[0148] The cellulose is glass fiber, and the diameter of the glass fiber is 10-20 μm and the length is 2-5 mm.
[0149] The bean dregs are obtained as follows:
[0150] Soaking and grinding the soybeans and filtering them to obtain a filter residue;
[0151] The filtered residue is dried and then ground to pass through a 200-mesh sieve, and the sieved material is taken to obtain bean dregs.
[0152] S403: pouring the filling adhesive material into the gap between the lower part of the assembly block and the ground, the gap between the assembly blocks, and the gap between the side of the edge assembly block and the wall;
[0153] S404 is cured, the curing temperature cannot be lower than 15℃, and the time is 10 days.
[0154] First, separate the assembly blocks using a cutting machine, and use a lever to lift the outermost assembly block to measure the force applied, which is 635N.
[0155] The entire space was moistened for 24 hours, and the assembly block on the other side was lifted up with a lever to measure the applied force, which was 478N.
[0156] The above are only embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included within the scope of the claims of the present application.
Claims
1. A cement-based self-leveling filling adhesive material, characterized in that: Including the following raw materials by mass: Cement: 180-200 parts; Gypsum powder: 4-6 parts; Vitrified microspheres: 6-8 parts; Glass powder: 8-10 parts; Okara: 4-6 portions; Cellulose: 0.5-0.8 parts; Polycarboxylate ether: 0.3-0.5 parts.
2. A cement-based self-leveling filling adhesive material as claimed in claim 1, characterized in that: The water-to-material ratio of the filling adhesive material is 0.3-0.4:
1.
3. The cement-based self-leveling filling adhesive material according to claim 1, characterized in that: The particle size of the vitrified microspheres is 10-100 μm; The cellulose is glass fiber, and the diameter of the glass fiber is 10-20 μm and the length is 2-5 mm.
4. The cement-based self-leveling filling adhesive material according to claim 1, characterized in that: The glass powder is obtained by crushing silicate glass, and then sieving to obtain particles with a particle size between 20 mesh and 50 mesh.
5. The cement-based self-leveling filling adhesive material according to claim 1, characterized in that: The bean dregs are obtained in the following manner: Soaking and grinding the soybeans and filtering them to obtain a filter residue; The filtered residue is dried and then ground to pass through a 200-mesh sieve, and the sieved material is taken to obtain bean dregs.
6. The cement-based self-leveling filling adhesive material according to claim 1, characterized in that: The flexural strength of the mortar board obtained by pouring the filling adhesive material after being fully moistened is 1 / 3-1 / 2 of that in the dry state.
7. A method for constructing a cement-based self-leveling filling adhesive material, characterized in that: The steps include: Lay the assembly blocks on the ground and level the assembly blocks; preparing a filling bonding material; Pour the filling adhesive material into the gap between the lower part of the assembly block and the ground, the gap between the assembly blocks, and the gap between the side of the edge assembly block and the wall; After maintenance, install the floor heating pipes on the assembly blocks.
8. A cement-based self-leveling filling adhesive material construction method as claimed in claim 7, characterized in that: An introduction channel for introducing filling adhesive material is reserved in the middle of the assembly block.
9. A cement-based self-leveling filling adhesive material construction method as claimed in claim 7, characterized in that: The filling bonding material is prepared as follows: The cement, gypsum powder, vitrified microspheres and glass powder are fully mixed to obtain a first component; Adding dregs of soybeans, cellulose and polycarboxylate ether into water and mixing them thoroughly to obtain a second component; The first component and the second component are mixed to obtain a filling bonding material.
10. A cement-based self-leveling filling adhesive material construction method as claimed in claim 7, characterized in that: An adjusting bolt for adjusting the height is arranged under the assembly block or a bottom supporting leg is arranged at the bottom of the assembly block.